2015
DOI: 10.3389/fncel.2015.00126
|View full text |Cite
|
Sign up to set email alerts
|

Retinal aging in the diurnal Chilean rodent (Octodon degus): histological, ultrastructural and neurochemical alterations of the vertical information processing pathway

Abstract: The retina is sensitive to age-dependent degeneration. To find suitable animal models to understand and map this process has particular importance. The degu (Octodon degus) is a diurnal rodent with dichromatic color vision. Its retinal structure is similar to that in humans in many respects, therefore, it is well suited to study retinal aging. Histological, cell type-specific and ultrastructural alterations were examined in 6-, 12- and 36-months old degus. The characteristic layers of the retina were present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
5
14
0
Order By: Relevance
“…Electro-dense deposits were noticed especially in the inner collagenous layer, starting from the 12 months group. This was also reported by Szabadfi et al [34] who clarified that aged Bruch's membrane displays an increase in phospholipids, triglycerides, fatty acids and free cholesterol content which called advanced glycation end products.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Electro-dense deposits were noticed especially in the inner collagenous layer, starting from the 12 months group. This was also reported by Szabadfi et al [34] who clarified that aged Bruch's membrane displays an increase in phospholipids, triglycerides, fatty acids and free cholesterol content which called advanced glycation end products.…”
Section: Discussionsupporting
confidence: 70%
“…Significant thinning of the retina was also observed by Nadal-Nicolás et al [27]. On the contrary, Szabadfi et al [34] found increased OLM--ILM distance and IPL thickness in 36-month-old degu rat retinae. The authors explained their findings by the loose retinal structure observed in aging retinae.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Degus have been described as a novel AD-like animal model (Inestrosa et al, 2005;van Groen et al, 2011;Ardiles et al, 2012Ardiles et al, , 2013Castro-Fuentes and Socas-Pérez, 2013;Tarragon et al, 2013;Vega-Zuniga et al, 2013;Acosta et al, 2014;Du et al, 2015;Inestrosa et al, 2015;Szabadfi et al, 2015;Altimiras et al, 2017;Cisternas et al, 2018). However, investigators have also found that degus housed and bred under different conditions may result in different levels of AD-protein accumulation.…”
Section: Degus May Be An Accelerated Model Of Age-related Retinal Chamentioning
confidence: 99%
“…Elevated levels of amyloid beta (Aβ) proteins and the associated cell damage have been described in the aging eye and opened up the possibility of Aβ being a key constituent of age-related ocular pathologies (Hinton et al, 1986;Dutescu et al, 2009;Koronyo-Hamaoui et al, 2011;Koronyo et al, 2017). Several investigations using the Octodon degus (degus) have confirmed a role for Aβ peptides in diseases, including increased Aβ peptides and phosphorylated tau levels in the adult retina (Acosta et al, 2014;Du et al, 2015) or altered retinal structure with age (Szabadfi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%